Protective effects of olive oil phenolics oleuropein and hydroxytyrosol against hydrogen peroxide-induced DNA damage in human peripheral lymphocytes - Zorić Nataša; Kopjar Nevenka; Rodriguez Jadranka Vuković; Tomić Siniša; Kosalec Ivan (Acta Pharmaceutica)
This study investigates antioxidant capacity and protective effects of phenolic compounds oleuropein (OLP) and hydroxytyrosol (HT), present in olive oil and olive leaves, against H2O2-induced DNA damage in human peripheral lymphocytes. Antioxidant potency was determined using the measurement of radical-scavenging activity (ABTS∙+ assay), ferric reducing power (FRAP assay) and cupric reducing antioxidant capacity (CUPRAC assay). Both substances were found to be potent antioxidant agents due to their free radical-scavenging activities. Antigenotoxic effects of oleuropein and hydroxytyrosol against H2O2-induced damage in human lymphocytes were evaluated in vitro by alkaline comet assay. At tested concentrations (1, 5, 10 µmol L−1), oleuropein and hydroxytyrosol did not induce a significant increase of primary DNA damage in comparison with the negative control. Pretreatment of human lymphocytes with each of the substances for 120 min produced a dose-dependent reduction of primary DNA damage in the tested cell type. Hydroxytyrosol showed a better protective effect against H2O2-induced DNA breaks than oleuropein which could be associated with their free radical-scavenging efficacy.